Disharmony in Fishermen's Families in Blimbing Village: Perspective of Marriage Law - Andhika Septian Anharil Huda (Penerbit Hellow Pustaka, 2025)
This research was conducted because it was motivated by the occurrence of disharmony among fishing families in Blimbing Village, Paciran District, Lamongan Regency. Disharmony in question includes quarrels, lack of affection, child mischief, and even divorce. This is reinforced by the existence of divorce data at the Lamongan Regency Religious Court, that in 2023 until November the total number of divorces that occurred in Paciran District reached 148 cases. This type of research is field research Then the primary data in this research was obtained from interviews. Meanwhile, secondary data is obtained from various sources such as books, journals, laws, and so on. The results of this research explain that the views of fishing families regarding family disharmony vary. Then the factors causing disharmony among fishing families in Blimbing Village are different from each other. One of them is that the partner does not carry out their duties and obligations. So if reviewed based on Law no. 1 of 1974 and the Compilation of Islamic Law, the disharmony that occurs in fishing families in Blimbing Village is not in line with what is stated in these provisions, both in terms of the purpose of marriage and the rights and obligations of husband and wife.